Battery Cluster Reverse Logistics Challenges - Litera, Petr; Kopáčková, Hana (IEEE (Institute of Electrical and Electronics Engineers), 2024)
This paper explores three primary strategies that enhance not only the deployment of battery technologies through scalability and interchangeability but also examine their significant impact on reverse logistics flows. It delves into the critical role of modular battery design, advocating for the standardization of battery size, capacity, and the integration of blockchain technology in Battery Management Systems (BMS) to ensure traceability and security. Furthermore, the study will reveal specific conditions under which the cost of Going-To-Market (GTM) strategies can align with or equal the expenses associated with battery reverse logistics, offering insights into cost-effective and sustainable battery lifecycle management.
Výzvy reverzní logistiky bateriového klastru
Keywords: fixed battery; swappable battery; blockchain; secondary usage; recycling; logistics; sustainability; pevná baterie; vyměnitelná baterie; blockchain; sekundární použití; recyklace; logistika; udržitelnost